Validity of Electronic Signatures in Employment Agreements After Government Regulation Number 35 of 2021 and Law Number 1 of 2024 - Siahaan, Anggraini; Pribadi, Sandi Januar (Jurnal Indonesia Sosial Sains, 2025)
The development of digital technology has significantly impacted various fields, including law, particularly in employment agreements. A key innovation is using electronic signatures, which enhance the efficiency and effectiveness of drafting legal documents. However, in Indonesia, the implementation of electronic signatures faces challenges such as regulatory issues, technical barriers, and societal acceptance. This study analyzes the validity of electronic signatures in employment agreements under Government Regulation Number 35 of 2021 and Law Number 1 of 2024 concerning the Criminal Code. Using a normative juridical approach, the research examines electronic signatures' compliance with contract law principles and the legal validity outlined in Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law). The findings confirm that electronic signatures are legally recognized if they meet the criteria in Articles 5 and 11 of the ITE Law. Government Regulation Number 35 of 2021 and Law Number 1 of 2024 further support the legality of electronically signed employment agreements. However, challenges remain, such as low digital literacy and inadequate digital infrastructure. To overcome these, the study recommends improving digital literacy, strengthening data security, and enhancing regulations to support electronic signature adoption in employment agreements, ensuring their effective use in the digital era.